Agroеcological resourses of climat peculiarities of Volyn woodlands (Polissya) - Tarasiuk, Nyna A.; Tarasiuk, Fedir P.; Тарасюк, Нина Адамівна; Тарасюк, Федір Павлович (Вінницький національний технічний університет, 2009)
On the background of manifestation of global warmth processes on the planet & in particular, in moderate latitudes of northern hemisphere, the increase of thermal resources of investigated territories is determined.
Keywords: Agroеcological resourses; Volyn Polissya